Internetware A New Software Paradigm for Internet Computing - Mei, Hong; Lü, Jian (Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a comprehensive introduction to Internetware, covering aspects ranging from the fundamental principles and engineering methodologies to operational platforms, quality measurements and assurance and future directions. It also includes guidelines and numerous representative real-world case studies that serve as an invaluable reference resource for software engineers involved in the development of Internetware applications. Providing a detailed analysis of current trends in modern software engineering in the Internet, it offers an essential blueprint and an important contribution to the research on software engineering and systems for future Internet computing.